 $a{ x }^{ 2 }+bx+c=0\\ \\ a{ x }^{ 2 }+bx=-c\\ \\ { x }^{ 2 }+\frac { b }{ a } x=-\frac { c }{ a } \\ \\ { \left( x+\frac { b }{ 2a } \right) }^{ 2 }-{ \left( \frac { b }{ 2a } \right) }^{ 2 }=-\frac { c }{ a } \\ \\ { \left( x+\frac { b }{ 2a } \right) }^{ 2 }-\frac { { b }^{ 2 } }{ 4{ a }^{ 2 } } =-\frac { c }{ a } \\ \\ { \left( x+\frac { b }{ 2a } \right) }^{ 2 }=\frac { { b }^{ 2 } }{ 4{ a }^{ 2 } } -\frac { c }{ a } \\ \\ { \left( x+\frac { b }{ 2a } \right) }^{ 2 }=\frac { { b }^{ 2 } }{ 4{ a }^{ 2 } } -\frac { 4ac }{ 4{ a }^{ 2 } } \\ \\ { \left( x+\frac { b }{ 2a } \right) }^{ 2 }=\frac { { b }^{ 2 }-4ac }{ 4{ a }^{ 2 } } \\ \\ x+\frac { b }{ 2a } =\pm \frac { \sqrt { { b }^{ 2 }-4ac } }{ \sqrt { 4 } \sqrt { { a }^{ 2 } } } =\pm \frac { \sqrt { { b }^{ 2 }-4ac } }{ 2a } \\ \\ x=-\frac { b }{ 2a } \pm \frac { \sqrt { { b }^{ 2 }-4ac } }{ 2a } \\ \\ x=\frac { -b\pm \sqrt { { b }^{ 2 }-4ac } }{ 2a }$ $\frac { a }{ c } \pm \frac { b }{ c } =\frac { a\pm b }{ c } \\ \\ \frac { a }{ b } \pm \frac { c }{ d } =\frac { ad }{ bd } \pm \frac { bc }{ bd } =\frac { ad\pm bc }{ bd } \\ \\ \sqrt { { a }^{ 2 } } ={ a }^{ \frac { 2 }{ 2 } }=a\\ \\ \sqrt { a } \sqrt { b } =\sqrt { ab } \\ \\ \frac { \sqrt { a } }{ \sqrt { b } } =\sqrt { \frac { a }{ b } }$